Broadband Futures: Content, Connectivity and Control. Issue 1 (May 2014) - Allen, Matthew; Park, Sora; Middleton, Catherine; Thompson, Peter
This introduction to the Broadband Futures: Content, Connectivity and Control special issue begins with the claim that we are at the start of a new period of debate and analysis about network infrastructure and use that declares government failure and reinvigorates the drive to a free-market solution in Australia and New Zealand. But questions remain about the effectiveness and social value of network developments, regardless of the degree of government investment and regulation. As canvassed in this introduction, and the articles that make up the special issue, we can only move forward, both in research and practical implementation, if we accept the intricate weaving together of past, present and future interactions between governments, service providers and their consumers in broadband development.